O‐glycosylation of the novel SARS‐CoV‐2 coronavirus spike protein influences furin cleavage - Zhang, Liping (FASEB J, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is responsible for the pandemic that has affected millions of people worldwide. This virus contains a unique polybasic insertion (PRRA) within the spike protein, resulting in a novel furin cleavage site that has been shown to influence viral infectivity and syncytia formation in cell culture. This insertion also generates novel putative sites of O‐glycosylation, a protein modification that has been shown in other proteins to influence furin cleavage. Here, we define the specific members of the UDP‐GalNAc:polypeptide N‐acetylgalactosaminyltransferase (GALNT) family that are capable of glycosylating the novel SARS‐CoV‐2 coronavirus spike and examine their presence in human respiratory cells that are targets for SARS‐CoV‐2 infection. Moreover, we show that O‐glycosylation by specific members of the GALNT enzyme family modulates furin cleavage of the spike in vivo. Given the well‐established role of O‐glycosylation in the regulation of proteolysis, our results suggest that O‐glycosylation of SARS‐CoV‐2 may play roles in aspects of spike stability/processing, which may influence viral infectivity and tropism.